MEMBANGUN MASYARAKAT DEMOKRATIS MELALUI PENDIDIKAN KEWARGANEGARAAN - Nadziroh Nadziroh (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: Espectation which still be remained from Indonesia nation in order to get out of various crisses is improving and repairing education system. National education is aimed at developing the competence of student to become pious and religious human wich have civilized bahaviour and kindnes, healthy, knowledgeable, capable, creative, self-supporting, and become democratic citizen and responsible. Civic education owns the strategic role in forming democratic and responsible citizen and bulilding the democratic society. Hoped competences after undergoing civic education is the owning of a set smart action, full of responsibility from a citizen in relating to state, and also able to have a share in solving various problem faced by the society, nation and state as according to proffesion capacities of each.